A review on the fabrication of several carbohydrate polymers into nanofibrous structures using electrospinning for removal of metal ions and dyes. (15th January 2021) - Phan, Duy-Nam; Khan, Muhammad Qamar; Nguyen, Ngoc-Thang; Phan, Thanh-Thao; Ullah, Azeem; Khatri, Muzamil; Kien, Nguyen Ngoc; Kim, Ick-Soo
Highlights: Carbohydrate polymers fabricated into nanofibrous membranes using electrospinning. Chitosan, cellulose, alginate, pullulan, starch, and hyaluronic acid were focused on. As-spun, chemically modified, composite nanofibers applied in heavy metal removal. Organic nanofiber and inorganic/organic nanofiber systems used for dye adsorption. Photocatalysts incorporated into nanofibers employed for dye degradation. Abstract: Water contamination by heavy metals and dyes has been one of the most severe problems globally. Various techniques have been employed to remove these contaminants from water, including adsorption and photocatalysis, which are highly efficient and environmentally friendly approaches. The overuse of traditional petroleum-based plastics in the production of filtration systems aggravates the status quo due to negative impacts on the environment. Bio-based polysaccharide polymers with the green and benign features and potential for commercial applications have been employed as feasible alternatives to replace synthetic polymers and reduce environmental impacts. With unique chemical composition, molecular weights, and functional chemical groups such as hydroxyl, amine, and carboxyl groups, carbohydrate polymers show multitude potentials for dye and metal ion chelation. This review focused on the fabrication of carbohydrate polymers, such as chitosan, cellulose, alginate, pullulan, starch, and hyaluronic acid, into nanofibrous structures using the electrospinning method and their environmental applications.